Pelanggaran Hak Cipta Karya Cipta Lagu Atau Musik Yang Dibawakan Oleh Ovent Organizer Untuk Kepentingan Komersial - Yambormias, Merlinda Tabita; Kuahaty, Sarah Selfina; Balik, Agustina (PATTIMURA Law Study Review, 2024)
ABSTRACT: Copyright violations of songs or musical works often occur. In fact, songs or music really provide benefits to humans, but creators or copyright holders of songs or music have to take great pains to obtain their rights because many ordinary people, especially business actors, namely event organizers, use songs or music without permission commercially. Based on Article 9 of Law Number 28 of 2014 concerning Copyright, it can be seen that every person is prohibited from publishing works, duplicating works in all forms, translating works, adapting, arranging or transforming works, distributing works or copies thereof, performing works, announcing works, communication of works, and rental of works and it is prohibited to exercise economic rights without the permission of the creator or copyright holder and it is prohibited to carry out commercial performances of works. This research is normative juridical research carried out using a statutory approach and a conceptual approach. The sources of legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. The legal material collection technique used in this research was literature surveillance, and finally analyzed using qualitative methods. Based on the research results, legal protection for copyrighted works of songs or music is regulated in Law Number 28 of 2014 concerning Copyright, which protects the creator or copyright holder of songs or music. Song or music copyrighted works that are used by the Event Organizer for commercial purposes by the act of performing song or music copyrighted works without permission from the creator or copyright holder, are referred to as copyright infringement by violating economic rights. Legal protection for the creator or copyright holder of songs or music used by the Event Organizer for commercial purposes is for the creator or copyright holder of the song or music to collaborate with one of the LMKs so that a song or music copyrighted work can be legally protected and obtain economic rights, because if someone does not register as a member, economic rights cannot be granted until that person registers as a member of LMK.